Los placeres ocultos (1977) d’Eloy de la Iglesia : un manifeste contre l’hétérocentrisme au tout début de la transition démocratique espagnole - Emmanuel Le Vagueresse (Itinéraires)
The Spanish film director Eloy de la Iglesia has always been an opponent of Doxa and dogma of any kind, be they moral, sensual, sexual, but also political, national or patriotic. In Los placeres ocultos, his tenth feature-length film, the director defies more openly than ever the moribund (post-)Francoist censors, through the story of Eduardo, a closet homosexual but who is surrounded by prostitutes, and who suddenly tries to take under his wing a youth from a housing estate, Miguel, in order to help him climb the social ladder, while rising above his desire for the heterosexual—sometimes with difficulty—so as to help him attain the higher spheres of social success.Held back by the censors for several months, until its eventual release in May 1977, this film is a landmark for the cinematographic depiction in commercial films of the “gay question,” at a time when all seemed possible. Questioning the heterocentrism of the Spanish nation via a seemingly mainstream film at the onset of the Demographic Transition, the film received a cool reception from the critics, but was a box office hit. It ushered in a profusion of films on the subject that were more or less militant, but also voyeuristic, making the acceptance of the “ordinary” homosexual—rather than the “queer”—the symptom of the newfound liberty of an entire country moving towards Democracy.